Multirresistência microbiana e opções terapêuticas disponíveis - Queiroz, Geisiany Maria de [UNESP]; Silva, Lucélia Magalhães da [UNESP]; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2012)
Background and objectives: Due to antibiotics irrational use and the empiric administration, many microbial resistance problems become a new therapeutic challenge, causing elevated mortality rates. Among the microorganisms groups related with resistant infections are: methicillin-resistant and vancomycin-resistant Staphylococcus aureus, multi-resistant Enterococcus sp, penicillin-resistant Streptococcus pneumoniae, Klebsiella pneumoniae carbapenemase, carbapenem-resistant Pseudomonas aeruginosa and Acinetobacter baumanii and extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL). The aim of this work was carry out a review of scientific literature in order to discuss the emergence of multidrug-resistant microorganisms and the therapeutic options available in Brazil. Contents: New antimicrobials are launched in order to achieve effective treatment for resistant microorganisms infections. To discuss the most common resistance mechanisms, new therapeutic options available in Brazil and new guidelines for the use of these drugs. Conclusion: While the use of antimicrobial drugs to keep so irresponsible and the law for its use not met, the new drugs will be effective only temporarily, keeping constant the microbial multi-resistance problem.

Justificativa e objetivos: Devido ao uso irracional de antimicrobianos e a administração empírica, vários problemas de resistência microbiana surgiram como um novo desafio para a terapêutica, causando elevados índices de mortalidade. Dentre os grupos de micro-organismos relacionados a infecções resistentes destacam-se: Staphylococcus aureus resistente à meticilina e Staphylococcus aureus resistente à vancomicina, Enterococcus sp resistentes a diferentes classes de antimicrobianos, Streptococcus pneumoniae resistente à penicilina, Klebsiella pneumoniae carbapenemase, Pseudomonas aeruginosa e Acinetobacter baumanii resistentes aos carbapenêmicos e ainda as enterobactérias produtoras de β-lactamases de espectro ampliado (ESBL). O objetivo deste estudo foi rever na literatura científica a abordagem do surgimento de micro-organismos multirresistentes e as opções terapêuticas disponíveis no Brasil. Conteúdo: Novos antimicrobianos são lançados no mercado com o intuito de alcançar tratamento efetivo para infecções causadas por micro-organismos resistentes. Para abordar os mecanismos de resistência mais comuns, das novas opções terapêuticas disponíveis no Brasil e das novas diretrizes de uso desses fármacos. Conclusão: Enquanto o uso dos medicamentos antimicrobianos continuarem sendo de modo irresponsável e não for cumprida a legislação para seu uso, os novos fármacos serão eficazes apenas temporariamente, fazendo constante o problema da multirresistência microbiana.
Microbial multi-resistance and available therapeutic options
Keywords: Enterobacteriacae; Gram-positives; Gram-negatives; Multi-resistant microorganisms; New antibiotics agents; Enterobactérias; Gram-positivos; Gram-negativos; Multirresistência; Novos agentes antimicrobianos